Peer groups and children's development - Howe, Christine (Understanding children's worlds, 2010)
Peer groups in a cultural context -- Peer groups and classroom structure -- Performance and cooperation in classrooms -- Cooperative interaction and curriculum mastery -- Friendship, status, and centrality -- Individual differences in informal experiences -- Social and personal adjustment -- School performance revisited -- Implications for practice and future research